Bank capital, credit risk and financial stability in Kenya - Samuel Kiemo; Camilla Talam; Irene W. Rugiri (Kenya Bankers Association (KBA), 2022)
The paper sought to explore the role of bank capital in mitigating credit risk and promoting financial stability. To achieve this, we constructed a Financial Soundness Index to evaluate financial stability conditions. A Panel Vector Auto Regression Model was employed using annual bank-level data from 2001-2020 for 37 banks, to examine the effect of bank capital on credit risk and financial stability. Overall, financial stability index long-term trend shows banks remain resilient, despite the downward trend from 2011 and instability margins since 2016. The findings also reveal that bank capital, lowers credit risk and strengthens financial stability. The paper conclude that bank capital supports financial stability through mitigating credit risks, and recommends that authorities continue adopting and implementing appropriate capital policies to foster financial stability and promote bank lending.
Keywords: 330; Bank Capital; Credit Risk; Financial Stability; Panel Vector Auto Regression model